Pelaksanaan Pembelajaran Sejarah dengan Nilai-Nilai Nasionalisme di SMA Negeri 2 Lubuk Pakam - Lubis, Mira Ardilla; Sumantri, Pulung; Nababan, Surya Aymanda (Medan Resource Center, 2024)
This research aims to examine the process of implementing history learning with nationalist values at SMA Negeri 2 Lubuk Pakam, the strategies used by teachers in integrating nationalist values, the benefits obtained by students and the obstacles teachers face when the learning process takes place. Using qualitative methods with a case study approach. The data collection technique in this research went through three stages, namely observation, interviews, and documentation to collect data. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results obtained from this research show that history teachers at SMA Negeri 2 Lubuk Pakam are always able to understand how to provide teaching that is in line with current developments and technology, so that learning gets significant results and students also get quality learning. History teachers also use various strategies that can arouse students' interest in history lessons so that the learning process runs well. Obstacles encountered during the learning process can also be overcome well by teachers using various methods and approaches.